The role of quality of working life in regulatory alienation - الجادر سهير عادل; العاملي علاء باسم (Journal of Economics and Administrative Sciences, 2016)
Abstract The goal of this research is to know the quality of working life and its impact on the level of the organizational sense of alienation among a sample of teaching Anbar University in the center of Baghdad. Find and seek to achieve a number of cognitive and practical goals. Where the quality of work life constitutes one of the main sources to enable organizations of excellence in light of the volatile environment, as is one of alienation regulatory organizations avoid the phenomena that occur because of their negative effects on performance and thus achieve their goals. The most research problem in question the existence of the main deficiencies in the application of the concepts of organizational alienation and attention to the quality of work life and their role in the omission of the surveyed University To clarify the relationship between research key variables was drafted mainly by two assumptions branched (10) subset. Tool resolution has been adopted in data and information relating to research collection, it has been prepared based to a number of standards ready to use the runway (Likret) Quintet, was subjected to a test validity and reliability. And distributed to a sample of (75) teaching in Anbar, Baghdad University Center and data analysis research used statistical program Ready (SPSS) and program (EXCELL) One of the most used statistical tools in the analysis are: the percentage of recurrence, and the arithmetic mean and standard deviation, and coefficient of variation, and the coefficient Pearson correlation and simple linear regression. The study produced a number of conclusions Perhaps the most prominent of a correlation relationship between the dimensions of the quality of work life and organizational alienation, as it emerged that there are significant effect between the dimensions of the quality of work life and organizational alienation. And no statistically significant differences between the responses of the respondents about the impact of Aavadnoaah working life in the organizational alienation attributable personal and functional variables (gender, age, educational qualification, marital status, years of career service). In the framework of the discussion of research results made a number of recommendations.